The intestinal microbiota in aged mice is modulated by dietary resistant starch and correlated with improvements in host responses. Issue 2 (17th September 2012) - Tachon, Sybille; Zhou, June; Keenan, Michael; Martin, Roy; Marco, Maria L.
Abstract: Dietary interventions might prevent or reverse age‐related declines in health through modification of the activity and composition of the intestinal microbiota. As a first step toward more comprehensive evaluations of single dietary components on healthy aging, 16S rRNA gene amplicon sequencing was applied to determine the structure of the bacterial communities in the ceca of 20‐month‐old healthy mice fed energy‐controlled diets containing 0, 18, or 36% type 2 resistant starch (RS) from high‐amylose maize (HAM‐RS2). The cecal microbiota of mice fed a diet depleted in RS and containing the readily digestible carbohydrate amylopectin were dominated by bacteria in the Firmicutes phylum and contained low levels of Bacteroidetes and Actinobacteria. In contrast, mice fed diets containing HAM‐RS2 were colonized by higher levels of Bacteroidetes and Bifidobacterium, Akkermansia, and Allobaculum species in proportions that were dependent on the concentration of the dietary fiber. The proportions of Bifidobacterium and Akkermansia were positively correlated with mouse feeding responses, gut weight, and expression levels of proglucagon, the precursor of the gut anti‐obesity/diabetic hormone GLP‐1. This study showed that aging mice harbor a distinct microbiota, which can be modulated by RS and enriched for bacteria that are associated with improved health.